PENGARUH BOOK VALUE, DEBT TO EQUITY RATIO, DAN PRODUK DOMESTIK BRUTO TERHADAP EARNING PER SHARE PT.UNILEVER INDONESIA. Tbk - Rosdiana (Program Studi Magister Manajemen Fakultas Ekonomi Universitas Krisnadwipayana, 2019)
This research intended to further examine whether firm financial performance and economic macro indicators such Book Value, Debt to Equity Ratio and Gross Domestic Bruto have a positive or negative impact Earning Per Share in PT.Unilever Indonesia,Tbk. During period 2006-2015, with the analysis of data using multiple regression with F test to analyze the effect of simultaneous. The research showed that Book Value, Debt to Equity Ratio and Produk Domestik Bruto has significant influence toward Earning Per Share.